ANALISIS PENGARUH LOKASI, PERSEPSI HARGA, VARIASI BARANG DAN KUALITAS LAYANAN TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING : (Studi pada Toko Feny Indragiri Hilir) - Haryanto, Indung; Mathori, Muhammad (Jurnal Riset Manajemen Akuntansi Indonesia, 2025)
This study aims to analyze the influence of location, price perception, variety of goods and service quality on customer loyalty through customer satisfaction as an intervening variable at Feny Indragiri Hilir Store. The data in this study used questionnaires distributed to all Feny Store customers totaling 160 people so that the technique used was saturated sampling because the entire population was used as a sample. Data testing in this study used the smart pls 4 application with inner model testing (convergent validity, discriminant validity, composite reliability), outer model and hypothesis testing. The results of this study indicate that all variables, namely location, price perception, variety of goods and service quality have a positive and significant effect on customer loyalty and customer satisfaction. The customer satisfaction variable also acts as a mediator in the influence of location, price perception, variety of goods and service quality on customer loyalty.